High-frequency rTMS improves quality of life and depressive symptoms in Parkinson's disease: A case report. Issue 12 (December 2022) - Michael, Panayiota; Constantinou Juhasz, Sandra Blythin; Evagorou, Olympia; Psalta, Lilia; Mikellides, Georgios
Abstract: Introduction: Parkinson's disease (PD) is a common neurodegenerative disorder, characterised by both motor and nonmotor symptoms. There is currently no cure for PD, although there are several treatment options for relieving PD symptoms. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain stimulation therapy that shows promising results for the treatment of PD. Methods: Here, we present a patient with PD. We investigated whether an accelerate form of high-frequency (HF) rTMS on the contralateral side to the patient's main difficulties is clinically effective in treating health-related quality of life (QoL) symptomatology and depressive symptoms in PD as well as the long-term effects of rTMS in PD during the maintenance phase. Results: Results showed that HF-rTMS administered over the right primary motor cortex (M1) is a safe and well-tolerated treatment that improved the patient's health related QoL and depressive symptoms. These positive effects lasted at least five months post treatment. Conclusion: Therefore, HF-rTMS over the right M1 can be a possible treatment option for patients with PD, although further investigations are necessary to validate the findings of the present case report. Abstract : Parkinson's disease; Repetitive transcranial magnetic stimulation; High-frequency; Quality of life; Motor symptoms; Non-motor symptoms; Depressive symptoms.